THE ELECTRIC FIELD FORMULATIONS IN THE PLANE-KNIFE CONFIGURATIONS - Yoyo Wardaya, Asep; Nur, Muhammad (BERKALA FISIKA, 2011)
In this paper, we calculate enormous electric field produced by the plane-knife configuration of the plasma generator. The value of electric field is calculated by two ways of configurations, the first is the almost perpendicular form of the Capasitor plates and second the perpendicular one. The result of calculation is the plates perpendicular form will produce higher electric fields than the almost perpendicular case. Key words : Plasma generator,Â plane-knife configuration , electric field.